2018
DOI: 10.20944/preprints201803.0156.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Affecting MOOC Usage by Students in Selected Ghanaian Universities

Abstract: There has been widespread criticism about the rates of participation of students enrolled on MOOCs (Massive Open Online Courses), more importantly, the percentage of students who actively consume course materials from beginning to the end. This study sought to investigate this trend by examining the factors that influence MOOC adoption and use by students in selected Ghanaian universities. The Unified Theory of Acceptance and Use of Technology (UTAUT) was extended to develop a research model. A survey was cond… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
4
11
0
Order By: Relevance
“…In line with this, the result by Ahn et al (2007) also indicated that playfulness has a significant positive effect on individual attitude and behavioural intention to use online retailing. This finding is in agreement with that by Fianu et al (2018) showing that computer self-efficacy was found to have a significant positive effect on MOOC Usage Intention. Additionally, Pellas (2014) suggested that students with higher e-learning self-efficacy are more likely to use e-learning.…”
Section: Correlation Analysissupporting
confidence: 93%
See 3 more Smart Citations
“…In line with this, the result by Ahn et al (2007) also indicated that playfulness has a significant positive effect on individual attitude and behavioural intention to use online retailing. This finding is in agreement with that by Fianu et al (2018) showing that computer self-efficacy was found to have a significant positive effect on MOOC Usage Intention. Additionally, Pellas (2014) suggested that students with higher e-learning self-efficacy are more likely to use e-learning.…”
Section: Correlation Analysissupporting
confidence: 93%
“…This is consistent with that of a previous study, which confirmed that information quality and system quality had some influence on the intention to use the ClassStart (Thongsri, Shen, and Bao, 2019). Moreover, Sharma et al (2017) found that the main issue affecting the acceptance of learners was system quality (Ahn, Ryu, and Han, 2007;Fianu et al 2018;Wang, Wu, and Wang, 2009). Therefore, a successful e-learning system must have a high functionality with exceptional service quality.…”
Section: Multiple Linear Regressionsupporting
confidence: 90%
See 2 more Smart Citations
“…Yang et al (2017) investigated the factors that influencing learner continuation in using MOOC, the finding revealed that the factors that impact learner continuance in using MOOC are: (1) system quality, this factor measured the reliability and functionality of the MOOC, (2) course quality, this factor defined by the quality and up-to-date of course content, (3) service quality, refers to the support offers from the MOOC providers such as instructors and IT staff, (4) learner perception about ease of use MOOC; and (5) learner perception about the usefulness of MOOC. Fianu, Blewett, Ampong, and Ofori (2018) also examined the factors that impact the adoption and use of MOOCs on students (N= 204). The findings indicated that continuance intention to use MOOC is affected by system quality, computer self-efficacy, and performance expectancy.…”
Section: Literature Reviewmentioning
confidence: 99%